2007
DOI: 10.1088/1478-3975/4/3/003
|View full text |Cite
|
Sign up to set email alerts
|

Efficient degradation and expression prioritization with small RNAs

Abstract: Abstract. We build a simple model for feedback systems involving small RNA (sRNA) molecules based on the iron metabolism system in the bacterium E. coli, and compare it with the corresponding system in H. pylori which uses purely transcriptional regulation. This reveals several unique features of sRNA based regulation that could be exploited by cells. Firstly, we show that sRNA regulation can maintain a smaller turnover of target mRNAs than transcriptional regulation, without sacrificing the speed of response … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 19 publications
0
83
1
Order By: Relevance
“…Such a mechanism effectively described sRNA-target and miRNA-target interactions in bacteria (13) and eukaryotes (16), respectively. In bacteria, titration entails hierarchical crosstalk between common targets of sRNA (14) and prioritized sRNA target expression (17).…”
mentioning
confidence: 99%
“…Such a mechanism effectively described sRNA-target and miRNA-target interactions in bacteria (13) and eukaryotes (16), respectively. In bacteria, titration entails hierarchical crosstalk between common targets of sRNA (14) and prioritized sRNA target expression (17).…”
mentioning
confidence: 99%
“…From a quantitative standpoint, these interactions can be accounted for without significantly complicating the mathematical model (Box 1). This model suggests that this crosstalk may in fact be highly efficient and sensitive (55,56).…”
Section: The Many Targets Of Small Rnasmentioning
confidence: 83%
“…Recent quantitative studies of small RNA regulation focused on the implications of incomplete (or absent) srRNA recycling on the properties of target repression (55)(56)(57)(58)(59). Using simple kinetic models (Box 1) it has been demonstrated that srRNAs can impose a threshold for the activation of gene expression: a significant gene silencing is achieved when the rate of mature mRNA production is smaller than the threshold, and is effectively relieved above it (Fig.…”
Section: Small Rna Recycling Determines Its Functional Propertiesmentioning
confidence: 99%
“…Our analysis of two entangled feedback loops creates a framework for analyzing small molecule regulatory circuits composed of multiple entangled feedback loops. For instance, the regulation of iron in E. coli, although being dominated by interactions that form a socialist motif (14,31), also contains a positive feedback on the metabolism side involving usage of iron in FeS clusters (32). Preliminary investigation (data not shown) suggests that two metabolism loops, connected like this in ''parallel'' (as opposed to the ''series'' connection between a transport and metabolism loop), are additive in behavior.…”
Section: Two-loop Motifs Arementioning
confidence: 99%